2017
DOI: 10.1016/j.ijscr.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of severe reflux after sleeve gastrectomy using the LINX ® system: Technique and one year follow up case report

Abstract: HighlightsPrevalence of reflux after sleeve gastrectomy.Introduction of new device to treat reflux after sleeve gastrectomy.The use of LINX system in treating reflux after sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one followed the FDA eligibility criteria for MSA insertion. Seven, comprising a total of 427 patients and published after FDA approval, extended these criteria to include patients with a hiatus hernia greater than 3 cm or previous gastrointestinal surgery, to assess whether the device could be used in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Device erosions have rarely occurred and have been managed without sequelae 9 10. More recently, the MSA procedure has been successfully performed in patients with large hiatus hernia11 and in those presenting de novo GERD after sleeve gastrectomy 12…”
Section: Discussionmentioning
confidence: 99%
“…If GERD refractory to medical management does occur after sleeve gastrectomy, the traditional management is conversion to a Roux-en-Y gastric bypass as the gastric fundus can no longer be used to perform a fundoplication 25,30. MSA, an alternative and potentially safer procedure, has been found in some studies to be effective for GERD management in this specific postoperative setting 25,31. It has also been suggested that perioperative insertion of the Linx device during sleeve gastrectomy may be a reasonable prophylactic measure 32.…”
Section: Indication For Usementioning
confidence: 99%